2016
DOI: 10.1089/ten.tea.2014.0705
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Endochondral Bone Repair Using Human Osteoarthritic Articular Chondrocytes

Abstract: hOA chondrocytes can adopt an endochondral phenotype after passaging and TGF-β superfamily treatment. Engineered endochondral cartilage grafts can integrate with host bone, undergo ossification, and heal critical-size long-bone defects in a mouse model. However, additional methods to further enhance ossification of these grafts are required before the clinical translation of this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Promoting interaction between the implanted cartilage graft and the host has been shown to be a key consideration for endochondral bone repair strategies [56]. Here, for all histological staining it was evident that the incorporation of printed microchannels enhanced host interaction in vivo.…”
Section: Discussionmentioning
confidence: 75%
“…Promoting interaction between the implanted cartilage graft and the host has been shown to be a key consideration for endochondral bone repair strategies [56]. Here, for all histological staining it was evident that the incorporation of printed microchannels enhanced host interaction in vivo.…”
Section: Discussionmentioning
confidence: 75%
“…Wnt and NGF signaling have been major therapeutic targets to inhibit the progression and pain associated with osteoarthritis 72,75,76 . Our group has previously exploited these parallels by engineering osteoarthritic cartilage to promote endochondral bone repair 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Survival mechanisms against hypoxia include autophagy, which is a common mechanism for the removal of excess or damaged organelles in the process of development and aging (6). On the other hand, previous studies had shown that the autophagy could promote the chondrocyte differentiation and hypertrophy of chondrocytes (7,16).…”
Section: Mag Induced Autophagy and Promoted Autophagic Flux In Bmsc-dmentioning
confidence: 99%